JEJAK SEJARAH PENULISAN AL-QUR’AN - Pakhrujain Pakhrujain; Habibah Habibah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
The writing of the Qur'an began at the time of the Prophet. However, the Qur'an is more memorized than written because the ability of the Companions radhiyallahu 'anhum is very strong and fast, and the number of memorizers is very large. At the time of the Prophet SAW, the Qur'an was still written on the fronds of dates, boards, animal skins, hard soil, stones and others.